Isolation of Francisella tularensis and Yersinia pestis from Blood Cultures by Plasma Purification and Immunomagnetic Separation Accelerates Antibiotic Susceptibility Determination - Aloni-Grinstein, Ronit; Schuster, Ofir; Yitzhaki, Shmuel; Aftalion, Moshe; Maoz, Sharon; Steinberger-Levy, Ida; Ber, Raphael (Frontiers in Microbiology, 2017)
The early symptoms of tularemia and plague, which are caused by Francisella tularensis and Yersinia pestis infection, respectively, are common to other illnesses, resulting in a low index of suspicion among clinicians. Moreover, because these diseases can be treated only with antibiotics, rapid isolation of the bacteria and antibiotic susceptibility testing (AST) are preferable. Blood cultures of patients may serve as a source for bacteria isolation. However, due to the slow growth rates of F. tularensis and Y. pestis on solid media, isolation by plating blood culture samples on proper agar plates may require several days. Thus, improving the isolation procedure prior to antibiotic susceptibility determination is a major clinically relevant need. In this study, we developed a rapid, selective procedure for the isolation of F. tularensis and Y. pestis from blood cultures. We examined drop-plating and plasma purification followed by immunomagnetic separation as alternative isolation methods. We determined that replacing the classical isolation method with drop-plating is advantageous with respect to time at the expense of specificity. Hence, we also examined isolation by immunomagnetic separation. Sub-localization of F. tularensis within blood cultures of infected mice has revealed that the majority of the bacteria are located within the extracellular fraction, in the plasma. Y. pestis also resides within the plasma. Therefore, the plasma fraction was isolated from blood cultures and subjected to an immunomagnetic separation procedure using polyclonal anti-F. tularensis live vaccine strain (LVS) or anti-Y. pestis antibodies conjugated to 50-nm nano-beads. The time required to reach an inoculum of sufficient bacteria for antibiotic susceptibility testing was shortest when using the plasma and immunomagnetic separations for both bacteria, saving up to 2 days of incubation for F. tularensis and 1 day for Y. pestis. Our isolation procedure provides a proof of concept for the clinical relevance of rapid isolation for AST from F. tularensis- and Y. pestis-infected patients.